2010
DOI: 10.1186/1476-4598-9-26
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptaibols, novel suppressors of tumor cells, targeted calcium-mediated apoptosis and autophagy in human hepatocellular carcinoma cells

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the most common cancers in the world which is highly chemoresistant to currently available chemotherapeutic agents. Thus, novel therapeutic targets are needed to be sought for the successful treatment of HCC. Peptaibols, a family of peptides synthesized non-ribosomally by the Trichoderma species and other fungi, exhibit antibiotic activities against bacteria and fungi. Few studies recently showed that peptaibols exerted cytotoxicity toward human lung epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 49 publications
4
57
0
4
Order By: Relevance
“…Alamethicin, an archetypical peptaibol, was eightfold less potent than 1 against PANC-1 cells (SI Appendix, Table S19). This agrees with widely reported cytotoxic properties described for most known peptaibols (18)(19)(20)(21)(22)(23)(24)(25). To provide an overall better understanding of the antiproliferative and cytotoxic properties of 1, the 10 helix is shown that was generated with Φ-and Ψ-angles of −49°and −29°for poly-Ala dodecamer using the PepMake 1.2 server at pepmake.wishartlab.com/.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…Alamethicin, an archetypical peptaibol, was eightfold less potent than 1 against PANC-1 cells (SI Appendix, Table S19). This agrees with widely reported cytotoxic properties described for most known peptaibols (18)(19)(20)(21)(22)(23)(24)(25). To provide an overall better understanding of the antiproliferative and cytotoxic properties of 1, the 10 helix is shown that was generated with Φ-and Ψ-angles of −49°and −29°for poly-Ala dodecamer using the PepMake 1.2 server at pepmake.wishartlab.com/.…”
supporting
confidence: 81%
“…T2, the fungus was grown in several types of broth media. Growth of the fungus in a modified potato dextrose broth (PDB) resulted in the generation of numerous new and known members of the malettinin family of polyketides [malettinins A (27), B (28), and F-H (16)(17)(18)(19)(20), respectively] ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Although functional autophagy acts as a metabolic stress buffer, many lines of evidence support a role for autophagy in antagonizing cell survival and in promoting cell death and apoptosis. [18][19][20] Autophagy has an important role in cancer, and inhibition of this cellular process has been proposed to contribute to HCC progression, 21,22 and, therefore, it is a potentially very important target for liver cancer prevention and treatment.…”
mentioning
confidence: 99%